Management and education in terms of globalization - Langovic Milicević, Ana; Cvetkovski, Tatjana; Langović, Zlatko (Hotel and Tourism Management, 2013)
The new society could be reffered to as learning society, and being so it demands different types of knowledge that lead to getting employment. Industry development is in a high degree influenced by education which is to develop a worker skillfulness which further increases his/her mobility and job security. It is of utmost importance for companies to have employees who are able to respond to rapid and enormous changes thus strengthening their competence and development. Educational results are not reflected on individuals only, but on a society as a whole. There are numerous reasons influencing changes in education, e.g. a constant development and introduction of new technologies as well as globalization conditions which impose the cognition of cultural diversity.